Implement of M-Government to Improve Public Services - Ahmad Cucus; Yuthsi Aprilinda (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The Indonesianpopulationis one of themobilephone usersin theworldwithlarge numbers,the use ofmobilephonesdoesnât useasa toolof communicationbut itcanbe improvedas a liaison betweengovernmentandcitizen, the use ofmobile technologyis a one ofmediastoimprovegovernmentservicesthat has been conductedinvariousplacesin theworld, as an exampleforIndonesianto participate in developingmobile-based governance.The use ofmobile technologythat is easyandinexpensiveto be one ofthe advantagesobtainedifweapply them-government, the line betweengovernmentandcitizento bemore openwiththetwo-way communicationwith amobile-based service conceptcan be done anywhereand anytime. Expectedwiththe implementation ofm-government governancemore transparentandmore effective servicescan be realized.